Gestão da informação e políticas públicas : um estudo na prefeitura municipal de Campo Mourão - Silva, Rosely Sobral da (2008)
The Data Processing, consecrated in years 60 for the automatization of routine operational reports yielded its time the current Technology of the Information (IT), gift in the tactical and strategical actions of the organizations, for being winning the challenge to provide, to the borrowers of decisions, qualified information. In this scene of changes, as much the aspects technician as organizacionais go if improving under the point of view of the management of the information, demanding reevaluation of processes, qualification of human resources and appropriation of the vision of the information as strategical resource. This change in the way of if thinking IT is spread in such a way in the private organization as in the public, whose mission is turned toward the quality of the installment of the service, with raised degree of efficiency in the use of the available resources. The present work, pautado for a study developed next to the Municipal City hall of Campo Mourão, objective the analysis of the politics of investments and allocation of resources in IT, demanded currently of the public administration to take care of to the social demands, identifying to traces in the politics of management of people and organizacionais processes that also contemplate the estimated theoreticians of the management of the information of confrontation of the especificidades of the sector as, for example, the successory processes. In relation to the metodológicos procedures, the study it is characterized as exploratório-description, of qualitative matrix with longitudinal perspective. Interviews half-structuralized with the managers of IT, representatives of the secretariats and employees of the municipal administration for collection of primary data and documentary research for the collection of secondary data had been carried through. The analysis of the data allowed to characterize the project of technological modernization in its phase of implementation of the politics of IT. The study it identified to one strong trend in the boarding of technological aspects and administration of financial resources in relative exaggeration with the specific boarding in the field of the management of people and detected that the discontinuity in the execution of projects and politics in the municipal public administration is, still, one of the biggest problems for the organizacional management in these spaces.